KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN PERBANKAN DI SURAKARTA - TRIO HANDOKO (MANAJEMEN DAN KEUANGAN, 2004)
This study is aimed to know: bank attribute and customer internal factor influencing a customer in choosing a bank. Reserach method is used survei method and sampling technique is random sampling consist of 60 customers of gifted saving account or daily rate saving account that consist of variety of age, income, educational background, and accupation. Data analysis technique is used in this research qualitative analysis and quantitive analysis. With analytical tools like validity test, realibility test, correlation of product moment and chi square, it can be conclude taht hypothesis in this study is proved, there is difference based on customer internal factor to bank attribute by a customer in choosing a bank. So, the suggestion presented here is the bank can use the customer internal factor and bank attribute as regarding matter ti create marketing program hoped to operate effectively and efficiently.